2018
DOI: 10.1021/acsami.8b09982
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Thermal Interface Materials: Directional Heat Transfer in Uniaxially Oriented Liquid Crystal Networks

Abstract: For the development of anisotropic thermal interface materials (TIMs), a rod-shaped reactive monomer PNP-6MA is newly designed and successfully synthesized. PNP-6MA reveals a smectic A (SmA) mesophase between crystalline (K) and isotropic (I) phases. PNP-6MA can be oriented under a magnetic field ( B = 2 T), and its macroscopic orientation can be robustly stabilized by in situ polymerization. Even without macroscopic orientations, the fabricated thermal conducting liquid crystal (TCLC) films show the outstandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 40 publications
0
49
0
Order By: Relevance
“…Although bulk polymer materials are generally regarded as poor heat conductors, an individual polymer chain or a chainaligned polymer fiber is believed to have very high thermal conductivity. 9,10 Researchers believe that excellent thermal conductivity can be realized by assembling the polymer chains in order. 11 To date, most of the theoretical and practical interest has focused on polyethylene (PE) due to its model simplicity and its C-C bond similarity to diamond, one of the most thermally conductive (above 1000 W m À1 K À1 ) materials in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Although bulk polymer materials are generally regarded as poor heat conductors, an individual polymer chain or a chainaligned polymer fiber is believed to have very high thermal conductivity. 9,10 Researchers believe that excellent thermal conductivity can be realized by assembling the polymer chains in order. 11 To date, most of the theoretical and practical interest has focused on polyethylene (PE) due to its model simplicity and its C-C bond similarity to diamond, one of the most thermally conductive (above 1000 W m À1 K À1 ) materials in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al 15 showed a discotic LC (DLC) polymer with a thermal conductivity of 3.0 W m –1 K –1 , which was photopolymerized using a thiol–ene reaction between DLC molecules. Their group 16 also reported 2.5 W m –1 K –1 for a smectic-A (SmA) LC film for use as a thermal interface material.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The insulating materials used in such devices require high thermal conductivity to improve the efficiency of heat dissipation. [5][6][7] In particular, the high anisotropy in thermal conductivity of the insulating materials are considered to be advantageous for the reliability and lifetime of electronic equipment by efficiently dissipating heat in the desired direction. The higher cross-plane thermal conductivity (λ ⊥ ) is thought to be important when the insulating materials are in the intermediate layer between the heat source and heat sink.…”
Section: Introductionmentioning
confidence: 99%